Secular trends of dental caries and association with nutritional status: a retrospective analysis of 16,199 Chinese students from three successive national surveys from 2010 to 2019 - Changfu Hao; Yudan Hao; Xiaomin Lou; Xiaolin Wang; Weiping Liu; Huijun Zhou; Xiaolei Ban; Wencan Wu; Xuejie Wang; Xian Wang (Frontiers Media S.A., 2024)
IntroductionThe prevalence of dental caries (DC) among students in developing countries has increased at an alarming rate, and nutritional status has been shown to be associated with DC in children and adolescents with inconsistent conclusions. We aimed to understand the trends of DC prevalence in students aged 7, 9, 12, and 14 years and to explore the relationship between DC prevalence and nutritional status.MethodsWe recruited 16,199 students aged 7, 9, 12, and 14 years in China by multi-stage, stratified, random sampling methods from 2010 to 2019. Permanent caries were measured using the Decay, Loss, and Filling (DMF) index and prevalence rate. Deciduous caries were measured using the decay, loss, and filling (dmf) index and prevalence rate. Nutritional status was assessed using body mass index (BMI) and hemoglobin levels. Logistic regression analysis was used to assess the association between nutritional status and the DC prevalence in children and adolescents, incorporating information concerning family-related factors.ResultsThe results indicated that DC prevalence increased from 39.75% in 2010 to 53.21% in 2019 in Henan province, with deciduous teeth and permanent teeth being 45.96 and 27.18%, respectively, in 2019. The total caries rate decreased with age (p < 0.05), and the caries rate of girls was higher than that of boys in 2019 (55.75% vs. 50.67%) (p < 0.001). The prevalence of dental caries among primary and secondary school students in areas with medium economic aggregate was the highest, followed by cities with the best economic development level, and cities with low economic levels have a lower prevalence of dental caries. The dental caries prevalence was negatively correlated with body mass index. In the fully adjusted model, underweight children had a higher caries prevalence (OR = 1.10, 95%CI: 0.86-1.41). Children with anemia had a higher prevalence of dental caries (OR = 1.18, 95%CI: 0.98-1.42).ConclusionThe DC prevalence of students in Henan Province was high, with a tendency to increase. Females, young individuals, and those with a higher economic level showed a positive correlation with the prevalence of caries. In the process of economic development, particular attention should be paid to early childhood caries prevention. Nutritional status should be taken seriously among children and adolescents, and the oral health system should be improved to keep pace with economic development.